Pendampingan Perhitungan Kapasitas Produksi pada UMKM Salad Barbar Purwakarta - Puspasari, Dewi; Aryati, Nurul Dewi (Jurnal PKM Manajemen Bisnis, 2025)
This study focuses on the production capacity planning of Barbar Salad Purwakartaa local culinary business established in 2018 and is known for its fresh fruit salad and innovative menu offerings such as Es Mabar, Es Pucok, Es Teler Durian, Es Barbar and Es Semangka drinks. This study emphasizes the importance of production capacity in optimizing operational efficiency and assisting management in making decisions related to production facilities, product lines, workforce, and equipment purchases. This study uses sales data analysis for the last three months (September, October, November 2024) using the Moving Average (MA) method to estimate future sales trends. Key findings include the calculation of Break Even Point (BEP) for the entire business and individual products, providing strategic insights for decision making related to production and sales. Overall, this report provides a comprehensive overview of the state of production capacity of Barbar Salad Purwakarta, identification of areas that need improvement, and strategic recommendations to optimize future business performance. Thus, this study is not only useful for the management of ‘Barbar Salad Purwakarta” in planning and decision making.